2018
DOI: 10.2139/ssrn.3178705
|View full text |Cite
|
Sign up to set email alerts
|

Gap-Filling Government Debt Maturity Choice

Abstract: Do governments strategically choose debt maturity to fill supply gaps across maturities? Building on a new panel data set of more than 9,000 individual Eurozone government debt issues between 1999 and 2015, I find that governments increase long-term debt issues following periods of low aggregate Eurozone long-term debt issuance, and vice versa. This gap-filling behavior is more pronounced for (1) less financially constrained and (2) higher rated governments. Using the ECB's three-year LTRO in 2011-2012 as an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Badoer and James [ 2 ] established that a gap-filling effect exists owing to the impact of long-term government bonds on long-term bonds of high-credit companies. Eidam [ 41 ] investigated the public debt of Eurozone countries and averred that this gap-filling effect is more significant in government(s) with low financial constraints and high credit. Huang et al [ 4 , 5 ] used corporate data from 69 countries to study public debt and found that public debt squeezes corporate investment by tightening corporate credit constraints.…”
Section: Literature Review and Theoretical Hypothesismentioning
confidence: 99%
“…Badoer and James [ 2 ] established that a gap-filling effect exists owing to the impact of long-term government bonds on long-term bonds of high-credit companies. Eidam [ 41 ] investigated the public debt of Eurozone countries and averred that this gap-filling effect is more significant in government(s) with low financial constraints and high credit. Huang et al [ 4 , 5 ] used corporate data from 69 countries to study public debt and found that public debt squeezes corporate investment by tightening corporate credit constraints.…”
Section: Literature Review and Theoretical Hypothesismentioning
confidence: 99%
“…On the other hand, Guibaud et al (2013) show that catering to maturity clienteles is an optimal issuance policy, as a welfare-maximizing government issues longer maturity debt when the fraction of long to short horizon investors increases. Additional evidence suggests that corporations n]and Eurozone governments engage in gap-filling behavior, issuing long-term debt at times when the supply of long-term government debt decreases (Greenwood et al, 2015;Eidam, 2017).…”
Section: Bond Market Segmentationmentioning
confidence: 99%
“…3 For analyses of euro area public bond markets not considering market access risks see Eidam (2017) or .…”
Section: Introductionmentioning
confidence: 99%